Spontaneous Intrauterine Gastric Perforation: A Rare Cause of Fetal and Neonatal Ascites - Harveen Kaur; Vineet Binu; C. N. Abdul Tawab; Shanu Chandran (Wolters Kluwer Medknow Publications, 2024)
Background: Ascites in the fetal period persisting into the neonatal period is a rare condition occurring due to a variety of causes, including urinary, bilious, chylous, congenital infections, peritonitis, gastrointestinal malformations, or metabolic diseases. Gastrointestinal malformations account for very few such cases. Clinical Description: We report a rare case of a preterm male newborn, delivered at 31 + 1 weeks with antenatal suspicion of fetal hydrops and oligohydramnios. The baby was born with isolated massive ascites with respiratory distress, though was hemodynamically stable. There was no pallor, and air entry was reduced in both lungs with normal cardiovascular evaluation. Management and Outcome: He underwent a complete evaluation for isolated fetal ascites, including echocardiography, ultrasound, and blood investigations. Erect abdominal X-ray showed air under the diaphragm, following which the newborn underwent laparotomy, which confirmed gastric perforation. Surgical repair resulted in the resolution of ascites. Postoperatively, supportive care, mechanical ventilation, total parenteral nutrition, and intravenous antibiotics were provided. The baby gradually tolerated enteral feeds by day 15 and was discharged on day 38. Conclusion: Gastric perforation in the intrauterine period should be kept as one of the differential diagnoses in newborns presenting with isolated ascites, the perforation may be spontaneous or idiopathic.